Ecofriendly K-decorated ZnO/Zn(Al, La)2O4 catalyst for hydrogen production – Effect of heterostructure on catalyst activity at steam‐lean process gas. (15th October 2021) - Antoniak-Jurak, Katarzyna; Kowalik, Paweł; Próchniak, Wiesław; Bicki, Robert; Michalska, Kamila; Słowik, Grzegorz
Graphical abstract: Highlights: The effect of ZnAlLa-LDH calcinations temperature on HT-WGS activity of K-decorated ZnO/Zn(AlLa)2 O4 mixed metal oxides. Significant impact of heterostuctural surface morphology of mixed oxides on HT-WGS activity at lower steam/dry gas ratios. High resistance of K-decorated ZnO/Zn(Al, La)2 O4 catalyst against HT-WGS process conditions. Abstract: The effect of ZnAlLa-LDHs calcinations temperature on physicochemical and catalytic properties of K-decorated Zn-Al-La mixed oxides for water-gas shift reaction was investigated. The fresh and spent catalysts were characterized using various methods including XRF, N2 adsorption, TG/DTG/MS, XRD, FT-IR, STEM-EDS and HRTEM. Catalysts activity tests were carried out in high-temperature water-gas shift (HT-WGS) reaction in kinetic regime within the temperature range of 330–400 °C and H2 O/dry gas molar ratio in the range of 0.5–1. The relationship between the structural, surface morphology of catalysts and the activity in the HT-WGS reaction was studied. The presence of ZnO-Zn(AlLa)2 O4 heterostructure decorated with potassium species enhances HT-WGS activity. Calcinations of ZnAlLa-LDH precursor at mild conditions creates a favorable morphology of the surface and results in relatively high activity similar to the standard HT-WGS catalyst (Fe-Cr-Cu). The highest activity in the HT-WGS reaction at lower steam/dry gas ratios was obtained for the ZnAlLa_600_K.